Designing a Syllabus of Writing Course Integrated by ICT Competencies and CEFR for English Education Study Program - Maulida, De Lara siti; Purnawati, Purnawati (English Language Education, Universitas Internasional Batam, 2024)
There have been standards required to be incorporated for education especially designing English syllabus. The standards are varied such as integrating Information and Communication Technology (ICT) and Common European Framework of Reference (CEFR) for language that have been applied as 21st century skill. Thus, this study explores the ICT competences and CEFR level incorporated in writing syllabus for English Study Program in Indonesian universities. Nine syllabuses of writing course from English Study Program in Indonesia have been selected purposely regarding the availability of the universities. All the writing syllabuses are identified as Basic Writing, Professional Writing, Creative Writing, and Academic Writing. The result found that; Basic Writing, the CEFR level was A1-A2, Professional Writing, CEFR level was A2-B1, Creative Writing, CEFR level was A2-B2, and Academic Writing, CEFR level was B2-C1. While ICT competences in entire.